Comprensión lectora y logros de aprendizaje en el área de ciencias sociales en estudiantes del quinto grado de secundaria de la Institución Educativa Nº 60756, Iquitos 2023 - Del Aguila Castillo, Blanca Ruth (2024)
The research establishes that there is a significant relationship between reading comprehension and learning achievements in Social Sciences for fifth grade high school students of Educational Institution No. 60756 of the Iquitos district during the 2023 school year. The research was of type relational and data collection was carried out with two questionnaires, the hypothesis test was carried out with Spearman. According to the assessment of fifth grade students, both reading comprehension and learning achievements are at high levels. 94,70% of the students demonstrated a high level of learning achievement, while 5,30% reached an average level. This highlights the need to continue improving and strengthening student participation in school activities that promote reading comprehension at its three levels: literal, inferential and critical. The results of the study indicate a significant relationship between reading comprehension and learning achievements, with specific data showing values of r=0.632, r=0.502, r=0.630 r=0.502; all with a significance less than 0.01. These findings confirm the proposed hypothesis, demonstrating that better reading comprehension correlates with greater learning achievements.